Density-dependent performance of larval and juvenile toads: Implications for amphibian conservation - Weber, Tobias; Ozgul, Arpat; Schmidt, Benedikt R. (Basic and applied ecology, 2024)
Density dependent carry-over effects from one life history stage to another can affect the dynamics of populations. Here we study such carry-over effects from the tadpole to the postmetamorphic juvenile stage in an endangered amphibian, the natterjack toad (Epidalea calamita). We raised tadpoles in outdoor aquatic mesocosms at four densities and assessed juvenile performance after metamorphosis in terrestrial mesocosms. High larval density reduced mass at metamorphosis by 50 % and doubled the length of the larval period. Survival was reduced at the high densities. Larger metamorphs had higher survival in terrestrial mesocosms and remained larger than cohort members at the end of the 30-day experiment. Because juvenile survival drives amphibian population dynamics, density-dependent carry-over effects to the juvenile stage are likely to affect population viability. We discuss the implications of the results for amphibian conservation practice, both pond construction programs and surveys of amphibian populations.